Vitamin D and disease severity in bronchiectasis. (March 2019) - Ferri, S.; Crimi, C.; Heffler, E.; Campisi, R.; Noto, A.; Crimi, N.
Abstract: Background: Bronchiectasis is a complex respiratory disease characterised by permanent dilatation of bronchi. Vitamin D plays a role in infective disease by modulating the inflammation. Patients affected by bronchiectasis are frequently Vitamin D deficient and it correlates with lung function decline. We want to understand if there is a correlation between Vitamin D and clinical and radiological severity of bronchiectasis. Methods: We included 57 patients (17 males/40 female with mean age 60 ± 12 years) between October 2017 and March 2018. We excluded patients with cystic fibrosis, traction bronchiectasis and reporting Vitamin D supplementation. Bronchiectasis severity index (BSI) and Bhalla score were calculated, blood inflammatory markers and Vit. D were measured and lung function tests were performed. Results: Vitamin D is deficient in 64% of patients, sufficient in 36% and normal in 7%. Mean BSI is 7.5 ± 5 and mean Bhalla score is 16 ± 4. Vitamin D levels correlate with Bhalla score (R 2 = 0.68, p < 0.001) and BSI (R 2 = 0.58, p < 0.0001). The correlation appears to be stronger than other markers of inflammation such as ESR and CRP [R 2 = 0.33, p = 0.001 and R 2 = 0.39, p = 0.001 respectively]. Conclusions: We consider Vitamin D as a good predictor of clinical and radiological severity of bronchiectasis. Highlights: Vitamin D deficiency was found in the majority of patients with bronchiectasis despite sufficient sun exposure. Vitamin D levels correlated with extension and severity of bronchiectasis, and with lung function decline. These correlations were stronger than those found for other inflammatory markers. Vitamin D is a good predictor of clinical-radiological severity of bronchiectasis irrespectively of the underlying etiology. Abstract : Take home message: Vitamin D deficiency is common in patients affected by bronchiectasis and it correlates to clinical and radiological severity, regardless of latitude.